Investigating the impact of self‐management behaviours on quality of life and fear of recurrence in head and neck cancer survivors: A population‐based survey. Issue 4 (12th February 2019) - Dunne, Simon; Coffey, Laura; Sharp, Linda; Desmond, Deirdre; Cullen, Claire; O'Connor, Jean; O'Sullivan, Eleanor; Timon, Conrad; Gallagher, Pamela
Abstract: Objectives: Emerging cancer‐survivorship research suggests that self‐management can lead to improved outcomes. However, research examining the impact of self‐management behaviours on quality of life (QoL) and fear of recurrence (FoR) in cancer survivors is lacking. This study investigated the relationship between self‐management behaviours and QoL and FoR following treatment for head and neck cancer (HNC). Methods: Postal surveys were sent to 734 eligible HNC survivors (ICD10 C01‐C14; C32) in the Republic of Ireland who were 12‐ to 60‐months post diagnosis. QoL and FoR were measured using the Functional Assessment of Cancer Therapy (FACT‐G and Head and Neck Cancer Subscale) measure and Fear of Relapse/Recurrence Scale, respectively. Seven self‐management behaviours were measured using the Health Education Impact Questionnaire. Results: Three hundred and ninety‐five HNC survivors completed surveys (50.3% response rate). After controlling for sociodemographic and clinical characteristics, self‐management behaviours accounted for 20% to 39.4% of the variance in QoL and FoR. Higher scores on positive and active engagement in life, constructive attitudes and approaches, and skill and technique acquisition were significantly associated with higher global QoL and lower FoR, whilst higher scores on positive and active engagement in life and constructive attitudes and approaches only were significantly associated with higher HNC‐specific QoL. Additionally, lower scores on self‐monitoring and insight were significantly associated with higher HNC‐specific and global QoL and lower FoR. Conclusions: The findings highlight the potential utility of self‐management interventions promoting active problem solving, positive self‐talk, and skill acquisition amongst cancer survivors. However, increased self‐monitoring may relate to negative outcomes in HNC, a finding that warrants further investigation.